Factors Affecting the Oral Healthcare-seeking behavior of call center agents in Arriva Medical Philippines - Buchan, Patricia Pamela G.; Cruz, Patricia Grace G. (Department of Community Dentistry, University of the Philippines Manila, 2017)
INTRODUCTION: Healthcare-seeking behavior is the decision to engage in the utilization of healthcare systems. Factors such as socio-economic variables, demographics, type of illness, access to services, and perceived quality of services influence this behavior (MacKian,2003). Call center agents are those who handle incoming/outgoing calls for a business, account inquiries, and customer complaints. Their environment poses concerns in their health including oral health.